Analyze the Optimal Management of Superior Mesenteric Artery (SMA) Occlusion - Takahashi, Tetsuya; Takemoto, Masaaki (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2014)
Subjects and methods：The characteristics of patients with SMA occlusion in this hospital between October 1, 2005 and September 30, 2012 were investigated retrospectively. Results: There were 10 cases of SMA occlusion, of which 4 were treated with interventional radiology (IVR), 2 required additional enterectomy after IVR treatment, and 4 were treated with enterectomy. The time from the onset to diagnosis was significantly shorter (6.8 hours vs. 29.1 hours, p<0.05) and the serum CRP significantly lower (0.5mg/dL vs. 13.9mg/dL, p<0.05) in the IVR group which showed improvement in response to the treatment (n=2) than in the intestinal necrosis group (n=8). The cutoff values of the two parameters were 2 hours and 0.2mg/dL, respectively. There were no abnormal findings on abdominal CT in the IVR group. Conclusion: IVR is considered as a worthwhile initial treatment modality in cases of SMA occlusion when the interval from onset to diagnosis is under 2 hours, the serum CRP is ≤0.2mg/dL, and abdominal CT reveals no abnormalities.